Research in Educational and Vocational Guidance in the Nordic Countries : Current Trends - Plant, Peter [Verfasser]; Christiansen, Lone Lonne [Verfasser]; Loven, Anders [Verfasser]; Vilhjalmsdottir, Gudbjörg [Verfasser]; Vuorinen, Raimo [Verfasser] (My University, 2003)
"The Nordic countries havefollowed slightly different, yet complementarypaths in terms of research in guidance. Thebalance between studies in guidance based onsociology, psychology, and even ethnologyvaries according to the research focus andtradition in each of the Nordic countries. Thisarticle covers main Nordic guidance researchissues with characteristic examples from thevarious countries under the headings ofStructures, Contents, and Values. " (author's abstract, IAB-Doku) ((en))
Keywords: L 5 Beratung & Orientierung; L 5.3 Bildungs(gang)beratung; T 1 Forschungsrichtungen; I 2.2.2 Osteuropa; Berufsberatung; Schullaufbahnberatung; Forschungsansatz; Skandinavien